Alliance with Hell: Romans vs Armenians and Arabs - Cinemre, İlhami Tekin (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
After the fall of the Sāsānian Empire, Armenians under Arab pressure asked for help from the Roman Emperor Constans II, whereupon, declared Tʿēodoros Ṙštuni as patrik and then tried to tie the Armenian Church to Constantinople. Armenians, however, rejected the attempt and formed an alliance with Arabs. Sebēos, Armenian historian and bishop noted, ‘All the Armenian princes made a pact with death and contracted an alliance with hell’. In this context, the purpose of this contribution is to indicate the choice of Tʿēodoros Ṙštuni between two poles, to emphasise the historical context of this ‘alliance with hell’, and to examine the gains and losses of the Armenians after this pact.